Case Study of Pump Failure Due to Rotor-Stator Interaction - Hideo Ohashi (International Journal of Rotating Machinery)
Fluiddynamic interaction between rotor and stator generates local pressure fluctuation and can be a cause ofstructural vibration of turbomachines. The interaction produces a spatial distribution of pressure fluctuation with a certain diametrical mode and propagating speed, known as rotating pressure field. When the frequency and mode of a rotating pressure field coincide with those of the structural vibration, a fluid-excited resonance takes place, leading to eventual severe structural damage. An example of such damage is described in detail using the case of PLR pump failure of a BWR plant.